2020
DOI: 10.3390/molecules25092158
|View full text |Cite
|
Sign up to set email alerts
|

Biocomposites of Bio-Polyethylene Reinforced with a Hydrothermal-Alkaline Sugarcane Bagasse Pulp and Coupled with a Bio-Based Compatibilizer

Abstract: Bio-polyethylene (BioPE, derived from sugarcane), sugarcane bagasse pulp, and two compatibilizers (fossil and bio-based), were used to manufacture biocomposite filaments for 3D printing. Biocomposite filaments were manufactured and characterized in detail, including measurement of water absorption, mechanical properties, thermal stability and decomposition temperature (thermo-gravimetric analysis (TGA)). Differential scanning calorimetry (DSC) was performed to measure the glass transition temperature (Tg). Sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…The high-water absorption capacity could be reduced in further studies by applying hydrothermal/soda treatment to the bagasse before 3D printing. This lowers the hemicellulose content of the bagasse that ultimately helps in reducing the swelling behavior of the fibers [59]. Since 3D printing provides customization of the product, the SCB material supply could be printed in the form of tableware and could be utilized for single-time use as the results of our flexural tests are compared with the CT on the 1st day.…”
Section: Applicability Testmentioning
confidence: 99%
“…The high-water absorption capacity could be reduced in further studies by applying hydrothermal/soda treatment to the bagasse before 3D printing. This lowers the hemicellulose content of the bagasse that ultimately helps in reducing the swelling behavior of the fibers [59]. Since 3D printing provides customization of the product, the SCB material supply could be printed in the form of tableware and could be utilized for single-time use as the results of our flexural tests are compared with the CT on the 1st day.…”
Section: Applicability Testmentioning
confidence: 99%
“…For this reason, the development of composites with BioPE polymeric matrix is of great importance, due to the potential for technological application and the reduction of environmental impacts [18]. There are works in the literature on polyethylene composites reinforced with jute [19,20], curauá [21], sisal [22,23], coconut ber [24,25], cotton [26], rice husk [27] and wood powder [28,29], suggesting good mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Da Silva Pinto et al [ 26 ] incorporated sugarcane fibers to PHB and reported a decreased brittleness. Ehman et al [ 27 ] produced Green-PE/sugarcane bagasse 3D-printed biocomposites using maleic anhydride as a compatibilizer. They reported improvements in the tensile strength and modulus.…”
Section: Introductionmentioning
confidence: 99%